Política nacional de alfabetização e a reconversão docente no curso alfabetização baseada na ciência (2019 - 2021) - Ribeiro, Sara Gabrielle Fonseca (2023)
The research falls within the field of literacy policies in Brazil, especially with regard to the training of literacy teachers under the National Literacy Policy (BRASIL, 2019). Its objective is to understand the fundamental guidelines and the meaning given to the training of literacy teachers in what the Science-Based Literacy (ABC) course proposes. The research also seeks to problematize the fundamental notions about literacy proposed by ABC, highlight the national and international references that supported such ABC proposals, investigate the theoretical-pedagogical bases that make up the course and its epistemological links, in addition to analyzing what the evidence refers to. scientific elements integrated into the course and what meaning is produced by them. It uses, as a methodological contribution, qualitative research of a documentary nature, in the light of historical materialism. It highlights that the PNA, during its period of validity, brought the approach of the phonic literacy method as the only methodology proven by “scientific evidence” for working with Brazilian children and strongly brought an ideology of positivist science, superior to the human sciences, having disregarding all Brazilian academic production in the field of literacy. It identifies that the pedagogical bases that “support” ABC are cognitive theories, which take into account the biologizing factor of learning, to the detriment of social factors, interaction with others, in addition to socioeconomic and racial issues, very present in Brazil. Thus, the research considers that the course links the modern and the archaic in an attempt to reconvert teaching, because by bringing an outdated literacy method, associated with new technologies, ABC tries to disfigure and reduce teaching, to the mere reproduction of activities exposed in the platform. In this way, the research understands that ABC is a training course for literacy teachers on a digital platform, with low quality content, planned and executed by institutions from another country, in Portuguese from Portugal, with “practical” video classes of activities carried out in the Portuguese context, it constituted a course offered by the MEC that aimed to hegemonically serve the PNA and its authors.